The Role of Personal Branding in Increasing Generation Z Career Success - Rahayu, Tina; Marka, Mira Meilia; Septanti, Annisya Lutfi; Nijwah, Izzah Sarirotun (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The rapid development of human communication and interaction contributes significantly to intergenerational differences. Today's workplace is occupied by mostly generation Z, a generation that is skilled in technology. The aim of this research is to describe and analyze the relationship between personal branding and increasing career success for generation Z through the use of social media, Islamic human values, and skills among final students at the Faculty of Economics and Business, Muria Kudus University. The research population was 3846 students with 116 students being used as research samples. The data collection technique uses a questionnaire distributed via a digital platform, namely Google Form. The analysis technique uses Structural Equation Modeling (SEM) which is operated through the Partial Least Squares (PLS) program. The results of this research show that the use of social media, Islamic human values, and skills have a significant positive effect on personal branding. Personal branding has a significant positive effect on generation Z's career success.